Analisis Harga Pokok Produksi Pada Usaha Kerajinan Manik-Manik Toraja Satu Set Kandaure Dan Sokkong Bayu Di Lembang Angin-Angin Kabupaten Toraja Utara - Alex, Jelitha; Lusdani, Westerini (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
Beadwork is a craft that is in great demand in the market share, this industry is engaged in the production of handicrafts. The purpose of this study is how to determine the cost of production in the Toraja beads craft business One Set Kandaure and Sokkong Bayu in Lembang Angin – Angin, North Toraja Regency. This type of research is a quantitative descriptive research, in which the researcher thoroughly records, analyzes, various facts and symptoms that have been obtained in the form of Analysis of Cost of Production in the Toraja Beads Craft Business in Lembang Angin-Angin, North Toraja Regency. The types of data in this study are primary data and secondary data. This study aims to understand the cost of production in the 2019 Toraja bead craft business. The results of this study indicate that the production price in the Toraja bead craft business is a set of kandaure of IDR 342,783. 333 and sokkong bayu Rp. 375,212.5 per set.